Use of ICT in pedagogical practices of teachers of the Faculty of Psychology of a public university in Argentina - Borgobello, Ana (2018)
This study aims to create and describe profiles of public university professors in Argentina based on their use of ICTs in pedagogical practices. The study used an online questionnaire that measures personal and academic characteristics, experiences, training and mediated forms of communication with students. Descriptive, multivariate and content analyses were performed. The results show three profiles with differential positions in techno-pedagogical aspects determined by the use of Facebook, WhatsApp and Virtual Platform. In the narratives, differential critical positions were observed according to each profile. The interpretation and discussion of results were contextualized ina scenario that is not favorable towards the use of ICT.